Body types following obesity surgery and skin re-contouring: A secondary level of analysis - Jo Gilmartin Joan Maclean; Jill Edwards (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Purpose: To identify body types and normative transformation after obesity surgery and body re-contouring. Methods: A qualitative secondary analysis was conducted involving 20 transcripts, extracted from one primary dataset containing interview data. A model of empirically grounded type construction was employed and adapted to analyse data.  Results: Four emerging body types were revealed including type 1 'identity disruption', type 2 'overcoming identity lag', type 3 'refining appearance' and type 4 'transformed new me'.  The findings shed light on the normative transformation process and the huge challenges that patients encounter. It is crucial to acknowledge that body types 1 and 2 experienced identity disruption and emotional turmoil, post body recontouring surgery. Contrastingly, types 3 and 4 showed strong determination and resilience throughout the transformation process despite embodied turbulence Conclusion: This study makes plain the huge rupture to identity, appearance and body image that respondents experienced post-surgery, with the majority in a constant changing body and state of flux. This result provides nurses and allied health professionals with new research and insight to develop novel body esteem educational programmes to empower this particular patient group.